Cytotoxicity, Antioxidant Activity, and Total Phenolic Content of the Ethanolic Leaf Extract of Hornstedtia conoidea Ridl - Barbosa, Gina Barbosa; Alinapon, Cresilda Vergara; Enot, Melania Manginsay; Baltazar, Gloria Jesusa Detecio; Buncales, Emma Orbita; Gultiano, Analyn Galo; Ang, Aileen May Gabule (Asian Journal of Biological and Life Sciences)
This study uncovers the potential benefits of the leaves of the less explored Philippine endemic Hornstedtia conoidea. This study aimed to determine the total phenolic content (TPC), total flavonoid content (TFC), total antioxidant activity (TAA), and cytotoxicity of the ethanolic leaf extract of the H. conoidea. TPC, TFC, and TAA were determined using the Folin-Ciocalteu method, aluminum chloride method, and phosphomolybdenum method, respectively. Cytotoxicity was determined via brine shrimp lethality assay (BSLA). The TPC, TFC, and TAA of the extract were 13.29 ± 0.32, 6.87 ± 0.26, and 261.60 ± 6.06 mg/g dry sample, respectively. The extract exhibited toxicity with LC50 of 24.61 mg/L based on BSLA. Ethanolic leaf extract of H. conoidea possesses antioxidative activity and cytotoxic properties.
Keywords: Antioxidant activity; Brine Shrimp Lethality Test.; cytotoxicity; Hornstedtia conoidea; Total phenolic content